#TITLE_ALTERNATIVE# - MAHFUZ DAULAY (NIM 12103020), ALFIN
In the effort to increase production effectiveness and efficiency of a mining process, sometimes we meet plenty of problems. One of that problems is the difference of nickel rate calculation between exploration and production data. That difference, if happens significantly, hence can bother production stability and change all-set mining plan. In this final project research, conducted a study to find-out rate difference level between exploration and production data on an operating mine. It is also expected that we can know genesa factors influencing that rate difference. The genesa factors of lateritic nickel deposit that studied in order to know its influences to nickel rate difference are climate, topography, bed-rock, structure and joint, chemical elements and vegetation, and also time. Data collecting for this study is conducted in 3 characterized-different mining fronts of nickel site mine in Tanjung Buli, East Halmahera, North Maluku. Data collected from the site are exploration result data, daily mining data, and daily production data. Rate difference level which analysed is the rate value of Ni, Fe, and SiO2. From data processing, the result of rate difference in Surty, West Oshin, and East Oshin, is still in fair range, dominant at 0.5%-0%. From conducted statistical and qualitative analysis, can be known that nickel rate variation among mining fronts caused especially because of bed-rock difference, that is Peridotite in Surty and Dunite in Oshin. Topography factor also gives big influence to nickel rate spreading, where high nickel rate will reside in downward slope while low rate nickel in steeper slope.